AAPHD 2002 Distinguished Service Award: Myron Allukian, Jr., DDS, MPH - Rebecca King, DDS, MPH (Blackwell Synergy, 2002)
The Distinguished Service Award is AAPHD’s highest and most prestigious award. It is presented to an individual for excellent and distinguished service to public health dentistry. The 2002 recipient of this award is Dr. Myron Allukian, Jr.